Importance of Natura 2000 sites for wintering waterbirds: Low preference, species' distribution changes and carrying capacity of Natura 2000 could fail to protect the species. (December 2018) - Musilová, Zuzana; Musil, Petr; Zouhar, Jan; Adam, Matyáš; Bejček, Vladimír
Abstract: Evaluating the species use of protected area networks is of considerable worldwide importance, especially as a feedback for policy-makers and the conservation community. Based on the data of an annual, citizen-science monitoring programme of long tradition (2004–2015), we test the hypothesis that the European Natura 2000 network protects high quality habitats preferentially settled by wintering waterbird species in a central European State (the Czech Republic). We analysed species-specific variables (protection status, flyway population trend and numbers, geographical distribution, and foraging guild) explaining the proportions of numbers in Natura 2000 and individual-species changes in numbers inside and outside Natura 2000. The proportions of numbers in individual species were generally low in Natura 2000 sites. The observed pattern revealed the expected higher preference of protected Annex I species for Natura 2000 sites compared to other species and showed foraging guilds having significant differences in Natura 2000 preference, with high preference in herbivores and fish-eaters and low preference in invertebrate-eaters compared to omnivores. Northern species also showed a high preference for Natura 2000. The predicted prevalence of a higher rate of increase, or lower rate of decrease, inside Natura 2000, indicating that Natura 2000 facilitated the species' distribution changes, was not shown; instead, the positive and negative trends inside Natura 2000 were almost equivalent. We concluded that the low preference for Natura 2000, the distribution changes shifting species outside Natura 2000, and limits to the carrying capacity of the protected network sites, could all make an issue in effectively safeguarding the non-breeding populations of waterbirds. The extension of the Natura 2000 network to facilitate their wintering requirements and distribution changes is therefore a high priority. Graphical abstract: Highlights: We evaluated wintering waterbirds' response to 12 years of Natura 2000 implementation. We used citizen-science monitoring data. Herbivores and fish-eaters show high preference of Natura 2000 while invertebrate-eaters show the opposite. High preference does not necessarily mean higher trends in numbers inside the protected network.